Perlindungan Hukum Bagi Gelandangan Psikotik yang Terlibat Kekerasan (Studi Kasus di Dinas Sosial Kabupaten Banyumas): Legal Protection for Psychotic Homeless Individuals Involved in Acts of Violence (A Case Study at the Banyumas Regency Social Service Office) - Mahar, Revintalis Osilia; Wardani, Susilo (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
The issue of legal protection for psychotic homeless individuals involved in acts of violence is a critical matter in the context of human rights and state responsibility. This study aims to examine the legal protection available to psychotic homeless individuals who become either victims or perpetrators of violence in Banyumas Regency, as well as the challenges faced by the local Social Service Office in handling such cases. This research employs both normative and empirical approaches. The normative approach involves the analysis of relevant legislation and legal theories pertaining to the legal protection of psychotic homeless persons, with data collected through literature review of primary and secondary legal materials. The empirical approach is used to gather factual data on the implementation of legal protection in the field, conducted through interviews with relevant stakeholders, specifically the Banyumas Regency Social Service Office. The findings indicate that psychotic homeless individuals are entitled to legal protection through mechanisms stipulated in the Indonesian Civil Code, as well as the right to rehabilitation as regulated in Law No. 18 of 2014 on Mental Health and Banyumas Regency Regional Regulation No. 16 of 2015 on the Control of Social Problems. The main challenges encountered by the Social Service Office in handling psychotic homeless individuals include limited personnel, budget constraints, rejection by families, and societal stigma. Inter-agency cooperation and effective policy implementation are essential to ensure adequate legal protection for this vulnerable group.